Sistema de bibliotecas da Universidade Federal do Pará: plano de marketing - NASCIMENTO JÚNIOR, Carlos Alberto Souza do (2020)
Marketing has been applied as an important tool for academic libraries to reach their institutional and social goals. This marketing plan aims to propose the repositioning of the Libraries System (Sistema de Bibliotecas – SIBI) of the Federal University of Para (Universidade Federal do Pará – UFPA), coordinated by the Central Library (Biblioteca Central), which is presented as the biggest library networking system in Brazilian Amazon. As specific objectives, it seeks to analyse the marketing environment, to determine institutional objectives and goals and to define repositioning strategies through SIBI/UFPA’s marketing mix. It is developed using as its methodology focal group interview, brainstorms and systemized informational filtering. Through the analysis of the SIBI’s strengths, weaknesses, opportunities and threats, and so of its targeting, it proposes strategic actions of institutional marketing, endormarketing and promotional marketing, in order to consolidate, in its final, technical and internal public’s mind, as a stimulating working environment, as a technical and technological reference and a bridge between national and international institutions and the local information unities; and as a information networking system available to the whole academic community, acting based on convenience, speed and relevance.